Bridging DFM and Sourcing Strategy - Goel, Ganpati; Brahmbhatt, Rahul; Dhanagari, Mukesh Reddy (Eastasouth Institute, 2025)
This paper focuses on aligning Design for Manufacturing (DFM) principles with sourcing strategies to minimize one important step in rotor shaft manufacturing. The rotor shaft, an important part in high stress mechanical systems such as turbines or motors, is required to abstract and has to be designed and manufactured according to strict rules. Implementing DFM in the earlier phases of the design stream enables the production to be streamlined through geometric simplification, material selection, and process optimization. Early collaboration between design engineers and suppliers is necessary to integrate manufacturing capabilities into the required design to avoid the cost and delay of redesigns. The study aims to examine if the sourcing strategies affect DFM implementation. Technological strengths are used to select the suppliers so that materials and manufacturing processes match design specifications. Advanced machining techniques, additive manufacturing, and automation are key enablers of the DFM principle, minimizing the cost of production and lead time. The Supplier A and B case studies show how suppliers use rotor shaft production practices, advanced manufacture, and agile production for production efficiency. The study concludes that the success of DFM and sourcing strategies for rotor shaft manufacturing will need to be successful for rotor shaft manufacturing to be efficient, reduce costs, and maintain high-quality standards. Manufacturers are encouraged to work closely with suppliers, adopt flexible sourcing strategies, and invest in technology to remain competitive. The combination of the DFM principle and the latest strategies used for sourcing enables manufacturers to optimize production processes, reduce waste, improve the quality and performance of the product, and have a solid, economical supply chain.